„Gordonka” - Tornai, Katinka (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Following the advices of Thomas Gordon’s book, Teaching Children Self-discipline, I started to develop my competences in the field of assertive communication. I realized that this approach may be the key aspect of successful “personal development. Without extrinsic motivation assertive communication helps to base the communication and behavior concerning intrinsic motivation, the realization and understanding of feelings, and self-discipline. Through these processes of assertive communication students may fl ourish into more and more autonomous and responsible persons.